Mechanical Characteristics of Heishan Bentonite for Hazardous Waste Contamination Prevention - Xu, Jian-Hua; Li, Kai; Sun, Ke-Ming; Zhang, Shu-Cui (Frontiers in Earth Science, 2022)
A series of laboratory-based water infiltration tests at room temperature have been conducted to investigate the mechanical characteristics of Heishan bentonite as a potential backfill material. The experiments were performed with an oedometer testing apparatus which facilitates the mechanical loading, the water infiltration, and the deformation measurement. The results show that both swelling pressure-initial dry density and swelling strain-moisture content have an exponential relationship. Moreover, swelling strain dramatically decreases when the applied stress exceeds a reference stress of 100 kpa. Finally, permeability tests were carried on Heishan bentonite specimen and the studied material reaches an impermeable state when the moisture content is larger than 40%. The presented properties certificate that Heishan bentonite can be employed as a backfill material in engineering practice.